Anthropogenic influence on the 2018 summer warm spell in Europe: the impact of different spatio-temporal scales - Leach, N; Li, S; Sparrow, S; Van Oldenborgh, GJ; Lott, FC; Weisheimer, A; Allen, MR (American Meteorological Society, 2020)
We demonstrate that, in attribution studies, events defined over longer time scales generally produce higher probability ratios due to lower interannual variability, reconciling seemingly inconsistent attribution results of Europe’s 2018 summer heatwaves in reported studies.